Pyrolytic carbon coated reinforced phase ceramic powder as well as preparation method and application thereof
By covering the enhanced phase surface in additive manufacturing to pyrolyze the carbon layer, the problem of deterioration of powder fluidity and bulk density caused by enhancing the high specific surface energy in additive manufacturing is solved, and the integration of ceramic composite powder is improved performance.
Patent Information
- Application Number
- CN202411617922.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
In additive manufacturing, the high specific surface energy of the reinforced phase leads to a worsening of the fluidity and bulk density of the powder, which in turn affects the performance of the ceramic parts.
By adding the reinforced phase to a solution of phenolic resin and ethanol, and cleaving the phenolic resin during heating, a pyrolytic carbon layer is formed and coated on the surface of the reinforced phase, thereby improving the fluidity and bulk density of the powder.
It effectively solves the problem of deterioration in powder fluidity and bulk density caused by enhancing the high specific surface energy of the phase in additive manufacturing, improves the comprehensive performance of ceramic composite powders, and promotes the combination of the enhanced phase and ceramic matrix.
Smart Images

Figure CN119462175A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field related to advanced manufacturing of ceramic materials, and more specifically, relates to a ceramic powder with a pyrolytic carbon-coated reinforcement phase and a preparation method and application thereof. Background Art
[0002] Ceramic materials, metal materials and polymer materials are the three most widely used materials in today's society. Among them, ceramic materials refer to inorganic non-metallic compounds prepared by solid-phase sintering and liquid-phase sintering of natural or synthetic compounds. They are widely used in aerospace, automotive industry, optical ceramic products, electronics industry, biomedicine, chemical industry, textile, military and other fields, and play an important role in modern science and technology and economic and social development. Ceramic materials can be divided into two categories: ordinary ceramics and advanced ceramics. Among them, advanced ceramics have excellent mechanical properties such as high strength, high temperature resistance, corrosion resistance and wear resistance; in terms of electrical properties, they have advantages such as insulation, piezoelectric properties and semiconductor properties; in terms of biology, ceramic materials are easy to sterilize and have high mechanical strength and wear resistance. After implantation in the body, they will not cause immune rejection reactions and have good biocompatibility. In recent years, due to the development of the economy and society, the demand for high-performance complex structure ceramic parts has grown rapidly. However, due to the characteristics of high strength, high hardness and brittleness of ceramics, the processing and manufacturing of complex structure ceramic parts will be very difficult. Therefore, it is urgent to develop rapid manufacturing technology for complex structure ceramic parts with excellent performance.
[0003] To solve this difficulty, additive manufacturing technology that breaks through the limitations of materials and structures has emerged. Additive manufacturing is an intelligent manufacturing technology that accumulates materials layer by layer to manufacture three-dimensional structural entities based on digital models. Compared with traditional subtractive manufacturing (such as machining) and equal material manufacturing (such as casting, forging and welding), additive manufacturing technology has irreplaceable advantages in the manufacturing of complex structural parts. Among them, powder bed-based additive manufacturing technologies such as binder jetting and laser selective sintering have the characteristics of fast forming speed, wide range of material applications, high material utilization rate, and large forming size. Using these additive manufacturing technologies to form ceramics with complex structures has great prospects. In order to improve the performance of ceramic parts prepared using the above-mentioned various additive manufacturing technologies, adding reinforcement phases to ceramics is an effective method. Common reinforcement phases include whiskers, short fibers and nanoparticles. However, since these additive manufacturing processes are all carried out directly based on the powder bed, the performance of the powder directly determines the performance of the product. If the above-mentioned reinforcing phase is directly added to the raw powder, it will cause whiskers and fibers to break and shorten, reduce the fluidity and packing density of the powder, and other problems, causing the performance of additively manufactured parts to deteriorate and even make the process impossible to proceed. Summary of the invention
[0004] In view of the above defects or improvement needs of the prior art, the present invention provides a ceramic powder with a pyrolytic carbon-coated reinforcement phase and a preparation method and application thereof, which aims to solve the problem of deterioration of powder fluidity and packing density caused by the high specific surface energy of the reinforcement phase during additive manufacturing.
[0005] To achieve the above object, according to one aspect of the present invention, a method for preparing a ceramic powder having a pyrolytic carbon-coated reinforcement phase is provided, the method comprising the following steps:
[0006] A reinforcing phase is added to a solution obtained by mixing phenolic resin and ethanol to obtain a suspension, and the current suspension is heated to crack the phenolic resin to form a pyrolytic carbon layer on the surface of the reinforcing phase, thereby obtaining a ceramic powder of the reinforcing phase coated with pyrolytic carbon, which is suitable for additive manufacturing.
[0007] Furthermore, the current suspension is placed in a crucible and heated under a protective atmosphere to decompose the phenolic resin, so as to form a pyrolytic carbon layer on the surface of the reinforcement phase.
[0008] Furthermore, the temperature of the cracking and carbonization is 600°C to 1200°C, and the insulation time is 0.5h to 4h.
[0009] Furthermore, the material obtained by cracking is placed in a ball mill for ball milling, and then sieved and dried to obtain a ceramic powder with a pyrolytic carbon-coated reinforcement phase.
[0010] Furthermore, the ball milling time is 2 h to 36 h, the rotation speed is 200 rpm to 1000 rpm, and the filter screen is 50 mesh to 500 mesh.
[0011] Furthermore, the mass proportion of the phenolic resin in the solution is 25% to 75%.
[0012] Furthermore, the reinforcing phase is added to the dispersion medium, and ultrasonic dispersion and magnetic stirring are performed to obtain a suspension, the suspension is filtered, and the reinforcing phase obtained by filtration is fully dried, and the dried reinforcing phase is added to the solution.
[0013] Furthermore, the reinforcing phase refers to one or more of metal whiskers, oxide whiskers, ceramic whiskers, boride whiskers, inorganic salt whiskers, chopped carbon fibers, biofibers, chemical fibers, metal nanoparticles, and inorganic non-metallic nanoparticles; the dispersion medium refers to one or more of water, ethanol, a coupling agent, and a coupling agent solution; the stirring method used is constant temperature magnetic stirring, the magnetic stirring speed is 100rpm to 2000rpm, the temperature used is 10°C to 35°C, and the stirring time is 0.5h to 6h.
[0014] The present invention also provides a ceramic powder with a pyrolytic carbon-coated reinforcement phase, wherein the ceramic powder is prepared by the method for preparing the ceramic powder with a pyrolytic carbon-coated reinforcement phase as described above.
[0015] The present invention also provides a use of the above-mentioned pyrolytic carbon-coated reinforced phase ceramic powder in additive manufacturing of ceramic parts.
[0016] In general, compared with the prior art, the above technical solutions conceived by the present invention mainly have the following advantages over the prior art:
[0017] Beneficial effects:
[0018] 1. The current suspension is heated to crack the phenolic resin to form a pyrolytic carbon layer on the surface of the reinforcement phase, and then a ceramic powder of the pyrolytic carbon-coated reinforcement phase is obtained. The pyrolytic carbon layer on the surface eliminates the high specific surface energy characteristics of whiskers, fibers and nanoparticles, and improves the packing density and fluidity of the ceramic composite powder when applied to additive manufacturing, effectively solving the difficulty of manufacturing whiskers, fibers and nanoparticles reinforced and toughened ceramics based on powder bed additive manufacturing technology, and improving the comprehensive performance of the prepared ceramic powder.
[0019] 2. The pyrolytic carbon layer is easy to decompose at high temperature. The subsequent sintering stage can oxidize and completely eliminate the carbon at high temperature, or convert the carbon into other substances through chemical reactions, which promotes the bonding of the reinforcement phase and the ceramic matrix and achieves better strengthening and toughening effect.
[0020] 3. The preparation method is simple, low-cost, green and environmentally friendly, highly practical, easy to operate and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a flow chart of a method for preparing a ceramic powder with a pyrolytic carbon-coated reinforcement phase provided by the present invention;
[0022] Figure 2 is a scanning electron microscope image of the ceramic powder of pyrolytic carbon coated silicon carbide whiskers obtained in Example 1 of the present invention;
[0023] Figure 3 is a particle size distribution diagram of the ceramic powder of pyrolytic carbon-coated silicon carbide whiskers obtained in Example 1 of the present invention;
[0024] Figure 4 is a scanning electron microscope image of the ceramic powder of pyrolytic carbon coated silicon carbide whiskers obtained in Example 2 of the present invention;
[0025] Figure 5 This is a particle size distribution diagram of the ceramic powder of pyrolytic carbon-coated silicon carbide whiskers obtained in Example 2 of the present invention. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0027] See also Figure 1 The present invention provides a method for preparing a ceramic powder of a pyrolytic carbon-coated reinforcing phase. The preparation method forms a layer of pyrolytic carbon on the surface of the reinforcing phase by thermal cracking of a precursor phenolic resin, and then obtains a reinforcing phase powder coated with pyrolytic carbon of a suitable particle size by ball milling and sieving. The preparation technology has a simple process and a short preparation cycle. The pyrolytic carbon coating effectively solves the problem of poor powder fluidity and packing density caused by the high specific surface energy of the reinforcing phase during additive manufacturing. At the same time, powders with different particle size distributions can be obtained by adjusting the ball milling time. The pyrolytic carbon layer can be conveniently retained or completely eliminated as needed in the subsequent process flow. During the sintering process, it can be retained by protective atmosphere sintering or vacuum sintering, or the pyrolytic carbon layer can be completely eliminated by oxidation at an appropriate temperature, thereby enabling additive manufacturing of reinforced ceramic materials.
[0028] The preparation method mainly comprises the following steps:
[0029] S1, adding the reinforcing phase into the dispersion medium, and performing ultrasonic dispersion and magnetic stirring mixing to obtain a suspension.
[0030] The reinforcing phase refers to one or more of metal whiskers, oxide whiskers, ceramic whiskers, boride whiskers, inorganic salt whiskers, chopped carbon fibers, biofibers, chemical fibers, metal nanoparticles, and inorganic non-metallic nanoparticles. The purity of the whiskers is greater than 97%, the diameter of the whiskers is 0.1 μm to 2 μm, the length is 5 μm to 100 μm, the fiber diameter is 1 μm to 20 μm, the length is 5 μm to 200 μm, and the particle size of the nanoparticles is 1 nm to 20 μm.
[0031] The dispersion medium refers to one or more of water, ethanol, coupling agent, and coupling agent solution. The stirring method used is constant temperature magnetic stirring, the magnetic stirring speed is 100 rpm to 2000 rpm, the temperature used is 10° C. to 35° C., and the stirring time is 0.5 h to 6 h.
[0032] S2, filtering the obtained suspension, and fully drying the enhanced phase obtained by filtration.
[0033] S3, mixing phenolic resin and ethanol to obtain a solution, adding the dried reinforcing phase to the solution and stirring the mixture to obtain a suspension.
[0034] The mass proportion of the phenolic resin in the solution is 25% to 75%.
[0035] S4, placing the newly obtained suspension in a crucible, and heating it under a protective atmosphere to decompose the phenolic resin to form a pyrolytic carbon layer on the surface of the reinforcement phase.
[0036] The temperature of cracking and carbonization is 600°C to 1200°C, and the holding time is 0.5h to 4h.
[0037] S5, placing the obtained material in a ball mill for ball milling, and then sieving and drying, so as to obtain a ceramic powder with a pyrolytic carbon-coated reinforcement phase, wherein the ceramic powder is suitable for additive manufacturing.
[0038] The ball milling time is 2h to 36h, the rotation speed is 200rpm to 1000rpm, and the filter screen is 50 mesh to 500 mesh.
[0039] The present invention also provides a ceramic powder with a pyrolytic carbon-coated reinforcement phase, wherein the ceramic powder is prepared by the method for preparing the ceramic powder with a pyrolytic carbon-coated reinforcement phase as described above.
[0040] The present invention also provides an application of the pyrolytic carbon-coated reinforcing phase ceramic powder as described above in additive manufacturing of ceramic parts, such as binder jetting, laser selective sintering and other powder bed-based additive manufacturing technologies.
[0041] The present invention is further described in detail below with reference to specific embodiments.
[0042] Example 1
[0043] See also Figure 2 and Figure 3 The method for preparing the ceramic powder with pyrolytic carbon coated reinforcement phase provided in Example 1 of the present invention comprises the following steps:
[0044] (1) A silane coupling agent (KH550) and anhydrous ethanol were uniformly mixed at a mass ratio of 1:99 to prepare a solution, and then silicon carbide whiskers were added to the above solution and ultrasonically dispersed for 10 minutes. After dispersion, the solution was transferred to a magnetic stirrer and magnetically stirred for 0.5 hours. The whiskers had a diameter of 0.1 μm and a length of 5 μm.
[0045] (2) The obtained solution was filtered to take out the silicon carbide whiskers therein, and the silicon carbide whiskers were moved into a constant temperature drying oven at 70° C. and dried for 8 hours to completely dry them.
[0046] (3) Mixing phenolic resin and ethanol to obtain a solution, adding the dried reinforcing phase to the solution and stirring to obtain a suspension, wherein the mass proportion of the phenolic resin in the solution is 33%, and the whisker content in the suspension is 25%.
[0047] (4) The above suspension was poured into a crucible, placed in a high-temperature atmosphere furnace, and heated to 800°C at a heating rate of 5°C / min using argon as a protective gas, and then kept at this temperature for 2 h to fully carbonize the phenolic resin.
[0048] (5) The cooled powder is placed in a ball mill and subjected to high-speed ball milling at 350 rpm for 6 hours to grind the powder to a suitable particle size. The obtained powder is sieved through a 200-mesh sieve, and the large particles that do not pass through the sieve and are retained are the powder prepared by this method.
[0049] Example 2
[0050] See also Figure 4 and Figure 5 The method for preparing a ceramic powder with a pyrolytic carbon-coated reinforcement phase provided in Example 2 of the present invention comprises the following steps: S1, adding the reinforcement phase to a dispersion medium, and performing ultrasonic dispersion and magnetic stirring mixing to obtain a suspension. The diameter of the whisker is 2 μm and the length is 100 μm. The magnetic stirring speed is 100 rpm, the temperature used is 10°C, and the stirring time is 0.5 h.
[0051] S2, filtering the obtained suspension, and fully drying the enhanced phase obtained by filtration.
[0052] S3, mixing phenolic resin with ethanol to obtain a solution, adding the dried reinforcing phase to the solution and stirring to obtain a suspension, wherein the weight proportion of the phenolic resin in the solution is 25%, and the weight proportion of the reinforcing phase in the suspension is 50%.
[0053] S4, placing the newly obtained suspension in a crucible, and heating it under a protective atmosphere to pyrolyze the phenolic resin to form a pyrolytic carbon layer on the surface of the reinforcement phase. The pyrolysis and carbonization temperature is 600° C., and the holding time is 0.5 h.
[0054] S5, placing the obtained material in a ball mill for ball milling, sieving and drying, and obtaining a ceramic powder with a pyrolytic carbon-coated reinforcement phase. The ball milling time is 2 hours, the rotation speed is 200 rpm, and the filter screen is 50 mesh.
[0055] Example 3
[0056] The method for preparing the ceramic powder with pyrolytic carbon coated reinforcement phase provided in Example 3 of the present invention comprises the following steps:
[0057] S1, adding a reinforcing phase to a dispersion medium, and performing ultrasonic dispersion and magnetic stirring mixing to obtain a suspension. The reinforcing phase is one or more of whiskers, fibers and nanoparticles, the whiskers have a diameter of 2 μm and a length of 100 μm, the fibers have a diameter of 20 μm and a length of 200 μm, and the nanoparticles have a particle size of 20 μm. The magnetic stirring speed is 2000 rpm, the temperature used is 35° C., and the stirring time is 6 hours.
[0058] S2, filtering the obtained suspension, and fully drying the enhanced phase obtained by filtration.
[0059] S3, mixing phenolic resin with ethanol to obtain a solution, adding the dried reinforcing phase to the solution and stirring evenly to obtain a suspension, wherein the weight proportion of the phenolic resin in the solution is 75%, and the weight proportion of the reinforcing phase in the suspension is 75%.
[0060] S4, placing the newly obtained suspension in a crucible, and heating it under a protective atmosphere to pyrolyze the phenolic resin to form a pyrolytic carbon layer on the surface of the reinforcement phase. The pyrolysis and carbonization temperature is 1200° C., and the heat preservation time is 4 hours.
[0061] S5, placing the obtained material in a ball mill for ball milling, sieving and drying, and obtaining a ceramic powder with a pyrolytic carbon-coated reinforcement phase. The ball milling time is 36 hours, the rotation speed is 1000 rpm, and the filter screen is 500 mesh.
[0062] Example 4
[0063] The method for preparing the ceramic powder with pyrolytic carbon coated reinforcement phase provided in Example 4 of the present invention comprises the following steps:
[0064] S1, adding a reinforcing phase to a dispersion medium, and performing ultrasonic dispersion and magnetic stirring to mix to obtain a suspension. The reinforcing phase is one or more of whiskers, fibers and nanoparticles, the whiskers have a diameter of 1 μm and a length of 55 μm, the fibers have a diameter of 10 μm and a length of 100 μm, and the nanoparticles have a particle size of 10 nm. The magnetic stirring speed is 1000 rpm, the temperature used is 20° C., and the stirring time is 4 hours.
[0065] S2, filtering the obtained suspension, and fully drying the enhanced phase obtained by filtration.
[0066] S3, mixing phenolic resin with ethanol to obtain a solution, adding the dried reinforcing phase to the solution and stirring evenly to obtain a suspension, wherein the mass proportion of the phenolic resin in the solution is 50%, and the mass proportion of the reinforcing phase in the suspension is 50%.
[0067] S4, placing the newly obtained suspension in a crucible, and heating it under a protective atmosphere to pyrolyze the phenolic resin to form a pyrolytic carbon layer on the surface of the reinforcement phase. The pyrolysis and carbonization temperature is 1000° C., and the holding time is 3 hours.
[0068] S5, placing the obtained material in a ball mill for ball milling, sieving and drying, and obtaining a ceramic powder with a pyrolytic carbon-coated reinforcement phase. The ball milling time is 20 hours, the rotation speed is 500 rpm, and the filter screen is 200 meshes.
[0069] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a ceramic powder with a pyrolytic carbon-coated reinforcement phase, characterized in that: The method comprises the following steps: A reinforcing phase is added to a solution obtained by mixing phenolic resin and ethanol to obtain a suspension, and the current suspension is heated to crack the phenolic resin to form a pyrolytic carbon layer on the surface of the reinforcing phase, thereby obtaining a ceramic powder of the reinforcing phase coated with pyrolytic carbon, which is suitable for additive manufacturing.
2. The method for preparing a ceramic powder having a pyrolytic carbon-coated reinforcement phase according to claim 1, characterized in that: The current suspension is placed in a crucible and heated under a protective atmosphere to decompose the phenolic resin to form a pyrolytic carbon layer on the surface of the reinforcement phase.
3. The method for preparing a ceramic powder having a pyrolytic carbon-coated reinforcement phase as claimed in claim 2, characterized in that: The temperature of cracking and carbonization is 600°C to 1200°C, and the holding time is 0.5h to 4h.
4. The method for preparing a ceramic powder having a pyrolytic carbon-coated reinforcement phase according to claim 1, characterized in that: The material obtained by cracking is placed in a ball mill for ball milling, and then sieved and dried to obtain a ceramic powder with a pyrolytic carbon-coated reinforcement phase.
5. The method for preparing a ceramic powder having a pyrolytic carbon-coated reinforcement phase as claimed in claim 4, characterized in that: The ball milling time is 2h to 36h, the rotation speed is 200rpm to 1000rpm, and the filter screen is 50 mesh to 500 mesh.
6. The method for preparing a ceramic powder having a pyrolytic carbon-coated reinforcement phase according to any one of claims 1 to 5, characterized in that: The mass proportion of the phenolic resin in the solution is 25% to 75%.
7. The method for preparing a ceramic powder having a pyrolytic carbon-coated reinforcement phase according to any one of claims 1 to 5, characterized in that: The reinforcing phase is added to the dispersion medium, and ultrasonic dispersion and magnetic stirring are performed to obtain a suspension. The suspension is filtered, and the reinforcing phase obtained by filtration is fully dried. The dried reinforcing phase is added to the solution.
8. The method for preparing a ceramic powder having a pyrolytic carbon-coated reinforcement phase according to claim 7, characterized in that: The reinforcing phase refers to one or more of metal whiskers, oxide whiskers, ceramic whiskers, boride whiskers, inorganic salt whiskers, chopped carbon fibers, biofibers, chemical fibers, metal nanoparticles, and inorganic non-metallic nanoparticles; the dispersion medium refers to one or more of water, ethanol, coupling agent, and coupling agent solution; the stirring method used is constant temperature magnetic stirring, the magnetic stirring speed is 100rpm-2000rpm, the temperature used is 10°C~35°C, and the stirring time is 0.5h~6h.
9. A ceramic powder with a pyrolytic carbon-coated reinforcement phase, characterized in that: The ceramic powder is prepared by the method for preparing a ceramic powder with a pyrolytic carbon-coated reinforcement phase as described in any one of claims 1 to 8.
10. Use of the pyrolytic carbon-coated reinforced phase ceramic powder according to claim 9 in additive manufacturing of ceramic parts.
Citation Information
Patent Citations
Preparation method for carbon fiber surface composite coating
CN103031724A
Preparation method of boron-containing pyrolytic carbon layer on fiber surface
CN106007761A
Carbon fiber-reinforced ceramic-based composite material and a preparation method of same
CN107500796A
Fiber reinforced carbon-silicon carbide ceramic matrix composite material and preparation method thereof
CN109293383A
Production method of carbon fiber-reinforced ceramic-based compound material pyrolytic carbon interface layer
CN109987948A